76 Effects of concrete bit wear on drill handle vibration, drilling productivity and changes in bit tip geometry. (24th April 2018) - Rempel, David; Antonucci, Andrea; Botti, Lucia; Mora, Cristina; Martin, Bernard; Barr, Alan
Abstract : Introduction: The use of hammer drills for concrete drilling exposes construction workers to high levels of hand vibration that may lead to hand arm vibration syndrome and other musculoskeletal disorders. The aim of this study was to investigate the effects of concrete bit wear on drill handle vibration, productivity, and change in bit shape. Methods: A laboratory test bench system was used to automatically advance an active 8.3 kg hammer drill with a 1.9 cm diameter carbide-tipped bit into aged concrete block under feed force control to a depth of 7.5 cm while drill handle vibration (ISO 5349 and 28927) and penetration rate (mm/s) were measured. Bits were worn to 4 levels by consecutively drilling holes to cumulative depths of 0, 1900, 5700 and 7600 cm. Image analysis methods quantified 13 geometric parameters of the carbide tip. Changes in the geometric parameters were compared to changes in penetration rate. Result: Z-axis handle vibration increased significantly (p<0.05) from 4.8 to 5.1 m/s 2 (ISO weighted) and from 42.7 to 47.6 m/s 2 (unweighted) when comparing a new bit to a bit worn to 1900 cm of cumulative drilling depth, but did not increase further with more wear. Drilling time increased by 58% for the worn (5700 cm) bit compared to a new bit. Changes in bit shape highly correlated to reduced productivity were increased fluke slope, increased shoulder rounding, and decreased tip width. Discussion: Carbide-tipped bit wear was associated with a small increase in ISO weighted and unweighted z-axis handle vibration and a large decrease in drilling productivity. To reduce drill-handle vibration levels and exposure time to hand vibration, construction contractors should implement a bit replacement program guided by bit wear. Other controls, such as exposure time per day, may also be necessary to adequately protect workers from hazardous levels of hand vibration.